Lyotard, el arte y lo humano. A vueltas con lo irrepresentable: Lyotard, Art and Human. On the Unrepresentable - Vilar, Gerard (Universidad del Zulia, 2021)
What is human cannot be thought without that which annuls it, namely: the inhuman. Among the thinkers who have approached this question from an aesthetic point of view, Jean-François Lyotard stands out. What is inhuman is defined by contrast to what is human, but it is also defined by the problem of the representability of what we consider to be inhuman. Presentable, representable, unrepresentable are very central concepts in the thought of the late Lyotard. In the last ten years of his life, his philosophical program had to do with rewriting modernity, in carrying out his anamnesis, specifically thinking more deeply about the question of “Jews” and the significance of Auschwitz. Representing Auschwitz is a way of making the crime forget, because it cannot be represented without fail, since what that term designates as fact defies images and words. Lyotard stands on the side of those who defend the unrepresentability of the Shoah. This radicalism contrasts with the reality of numerous works of art that treat the Shoah as a paradigm of inhumanity. Against Lyotard's point of view, three main arguments will be given to defend the representability of the inhuman and its cognitive, ethical and political functions, so central in contemporary art.